ANALISIS PENGARUH DISIPLIN KERJA DAN TUNJANGAN KINERJA DAERAH TERHADAP KINERJA PEGAWAI DINAS KEPEMUDAAN, OLAHRAGA DAN PARIWISATA KOTA PRABUMULIH - Septianti, Dian (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2019)
This study aims to analyze the influence of work discipline and local performance benefits to the performance of employees of the Office of Youth, Sports and Tourism Prabumulih City. Data analysis methods used are qualitative and quantitative, with primary and secondary data sources in the form of questionnaires, interviews and documentation. The population of this study is all employees of the Department of Youth, Sport and Tourism Prabumulih with sampling technique is using saturated samples, where all the population sampled so that the sample in this study amounted to 32 respondents. The results showed that there was a significant influence between work discipline and regional performance allowance on the performance of employees of Youth, Sport and Tourism Office Prabumulih along with Sig 0,000. While some also found the influence of work discipline and performance allowance area with work discipline to be the most influential variable on employee performance.